ChewBBACA: A complete suite for gene-by-gene schema creation and strain identification. Issue 3 (15th March 2018) - Silva, Mickael; Machado, Miguel P.; Silva, Diogo N.; Rossi, Mirko; Moran-Gilad, Jacob; Santos, Sergio; Ramirez, Mario; Carriço, João André
Abstract : Gene-by-gene approaches are becoming increasingly popular in bacterial genomic epidemiology and outbreak detection. However, there is a lack of open-source scalable software for schema definition and allele calling for these methodologies. The chewBBACA suite was designed to assist users in the creation and evaluation of novel whole-genome or core-genome gene-by-gene typing schemas and subsequent allele calling in bacterial strains of interest. chewBBACA performs the schema creation and allele calls on complete or draft genomes resulting from de novo assemblers. The chewBBACA software uses Python 3.4 or higher and can run on a laptop or in high performance clusters making it useful for both small laboratories and large reference centers. ChewBBACA is available athttps://github.com/B-UMMI/chewBBACA .